Activity and pharmacology of homemade silver nanoparticles in refractory metastatic head and neck squamous cell cancer. Issue 1 (11th December 2018) - Singh, Jasmine; Moore, William; Fattah, Farjana; Jiang, Xingya; Zheng, Jie; Kurian, Pamela; Beg, Muhammad S.; Khan, Saad A.
Abstract: Background: Silver nanoparticles (AgNP) show efficacy in cancer cell lines. We present the first in‐human outcome of AgNP in a cancer patient. Methods: Homemade AgNP solution is manufactured using online instructions by a 78‐year old male. He started consuming AgNP while on hospice after he developed nasal cavity squamous cell cancer metastatic to liver and lung. Results: Electron microscopy of AgNP solution revealed bimodal nanoparticle size distribution: 3 and 12 nm. Inductively coupled plasma mass spectrometry showed basal silver ion concentrations of 32 ng/g, rising to 46 ng/g 1 hour after ingesting 60 mL of AgNP solution. Urine showed no AgNP. No toxicities were observed and he had complete radiographic resolution of his cancer. He remains without evidence of cancer 18 months later. Conclusions: AgNP ingestion was associated with sustained radiographic resolution of cancer. Further testing of AgNP should be done to confirm its efficacy in head and neck cancer.